MULTI-ELEMENT DETERMINATION FOR CRUDE OIL SAMPLES BY NUCLEAR ANALYTICAL METHODS - CAO , DONG VU; HO , MANH DUNG; NGUYEN , GIANG; DO , THANH THAO; LE , THI NGOC TRINH; NGUYEN , THI SY; TRAN, QUANG THIEN; HO , VAN DOANH; DUONG , HIEN LUONG (Nuclear Science and Technology, 2011)
This report presents the main results in multi-element characterization of trace element in crude oil sample by using nuclear analytical methods.